UJI KETAHANAN TERHADAP COWPEA MILD MOTTLE VIRUS PADA SEMBILAN BELAS POPULASI F1 TANAMAN KEDELAI (GLYCINE MAX [L.] MERRIL) HASIL PERSILANGAN DIALEL - Barmawi, Maimun; Utomo, Setyo Dwi; Akin, Hasriadi Mat; Ramli, Sulastri (JURNAL AGROTROPIKA, 2009)
The objective of this study was to evaluate the resistance to cowpea mild motlle virus (CPMMV) of 19 F1 population of soybean showing good agronomic characters. The F1 population were generated by complete diallel crosses involving a resistant parent (Mlg 2521), a moderately resistant parent (B 3570), and three susceptible parents (Orba, Wilis, and GKUL-1). The experiment was arranged in a completely randomized block design consisted of two replications. The results indicated that F1 population B 3570 x Mlg 2521 was resistant to CPMMV and superior in seed weight per plant, number of branches, plant height, total number of pods, total number of seeds, and the number of healthy seeds. F1 population Wilis x B 3570 and B 3570 x Wilis were moderately resistant and less superior in agronomic characters than B 3570 x Mlg 2521.Key words: CPMMV, diallel, Glycine max,viral resistance